2018
DOI: 10.1002/ange.201800288
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Catalytic Activation of Platinum and Ruthenium Anticancer Complexes by FAD and Flavoproteins

Abstract: Recent advances in bioorthogonal catalysis promise to deliver new chemical tools for performing chemoselective transformations in complex biological environments. Herein, we report how FAD (flavin adenine dinucleotide), FMN (flavin mononucleotide), and four flavoproteins act as unconventional photocatalysts capable of converting PtIV and RuII complexes into potentially toxic PtII or RuII−OH2 species. In the presence of electron donors and low doses of visible light, the flavoproteins mini singlet oxygen genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In our search for novel activation strategies, we recently showed that Rf and other flavins, including flavoproteins, can simultaneously act as photosensitizers and unconventional photocatalysts for the selective activation of anticancer metal-based prodrug candidates such as Pt IV complexes. These photocatalytic reactions efficiently deliver active Pt II species and take place by means of blue rather than UV-A light in the presence of zwitterionic buffers such as MES (2-(N-morpholino)ethanesulfonic acid), as well as with biological electron donors such as NAD(P)H 10 , 11 . Importantly, low doses of blue light are sufficient to fully convert high concentrations of Pt IV prodrugs in buffer solution and in cell culture medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our search for novel activation strategies, we recently showed that Rf and other flavins, including flavoproteins, can simultaneously act as photosensitizers and unconventional photocatalysts for the selective activation of anticancer metal-based prodrug candidates such as Pt IV complexes. These photocatalytic reactions efficiently deliver active Pt II species and take place by means of blue rather than UV-A light in the presence of zwitterionic buffers such as MES (2-(N-morpholino)ethanesulfonic acid), as well as with biological electron donors such as NAD(P)H 10 , 11 . Importantly, low doses of blue light are sufficient to fully convert high concentrations of Pt IV prodrugs in buffer solution and in cell culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, low doses of blue light are sufficient to fully convert high concentrations of Pt IV prodrugs in buffer solution and in cell culture medium. The Rf selectivity for Pt IV complexes demonstrated in the biological environment defines the bioorthogonal nature of these photocatalytic reactions 10 , 11 . According to our current understanding of the process (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an exciting prospect for flavins has been reported and shows that such derivatives can be used as efficient pro‐drug activators. Upon light‐activation, a flavin can be used as a catalyst to transform a metallo‐prodrug into its active species (Scheme ) . This flavin‐mediated bioorthogonal catalytic photoactivation of anti‐cancer metal complexes relies on a 2 electrons reduction of the flavin, along with a photooxidation of electron‐donor molecules.…”
Section: Bioinspired Catalysis Using Flavin Redox Cofactorsmentioning
confidence: 99%
“…Upon light-activation, a flavin can be used as a catalyst to transform a metallo-prodrug into its active species (Scheme 8). [62,63,64] This flavin-mediated bioorthogonal catalytic photoactivation of anti-cancer metal complexes relies on a 2 electrons reduction of the flavin, along with a photooxidation of electron-donor molecules. This doubly reduced flavin can then react and transfer electrons to a metal-based prodrug and catalytically generate in situ the actual metal-based drug needed for therapeutic action.…”
Section: Bioinspired Catalysis Using Flavin Redox Cofactorsmentioning
confidence: 99%
“…Tt-NOX presents high chemical and thermal stability, broad-range pH activity, and it can accept NADH or NADPH as substrates [3,10]. Thus, Tt-NOX has successfully been applied to cofactor regeneration systems in the kinetic resolution of secondary alcohols [10] and the selective oxidation of glycerol to yield 1,3-dihydroxyacetone [11,12], in the in situ production of H 2 O 2 coupled to immobilized preparation of peroxidase from horseradish to oxidize pollutants in aqueous solutions [13], in the activation of Pt IV and Ru II chemotherapeutic agents [14], and in biosensors [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%